Ganglionated Plexi Ablation Suppresses Chronic Obstructive Sleep Apnea-Related Atrial Fibrillation by Inhibiting Cardiac Autonomic Hyperactivation - Zhang, Ling; Guo, Yankai; Xiaokereti, Jiasuoer; Cao, Guiqiu; Li, Hongliang; Sun, Huaxin; Li, Kai; Zhou, Xianhui; Tang, Baopeng (Frontiers in Physiology, 2021)
Background: Previous studies have reported that right pulmonary artery ganglionated plexi (GP) ablation could suppress the onset of atrial fibrillation (AF) associated with obstructive sleep apnea (OSA) within 1 h. Objective: This study aimed to investigate the effect of superior left GP (SLGP) ablation on AF in a chronic OSA canine model. Methods and Results: Fifteen beagles were randomly divided into three groups: control group (CTRL), OSA group (OSA), and OSA + GP ablation group (OSA + GP). All animals were intubated under general anesthesia, and ventilation-apnea events were subsequently repeated 4 h/day and 6 days/week for 12 weeks to establish a chronic OSA model. SLGP were ablated at the end of 8 weeks. SLGP ablation could attenuate the atrial effective refractory period (ERP) reduction and decrease ERP dispersion, the window of vulnerability, and AF inducibility. In addition, chronic OSA leads to left atrial (LA) enlargement, decreased left ventricular (LV) ejection fraction, glycogen deposition, increased necrosis, and myocardial fibrosis. SLGP ablation reduced the LA size and ameliorated LV dysfunction, while myocardial fibrosis could not be reversed. Additionally, SLGP ablation mainly reduced sympathovagal hyperactivity and post-apnea blood pressure and heart rate increases and decreased the expression of neural growth factor (NGF), tyrosine hydroxylase (TH), and choline acetyltransferase (CHAT) in the LA and SLGP. After SLGP ablation, the nucleotide-binding oligomerization domain (NOD)-like receptor signaling pathway, cholesterol metabolism pathway, and ferroptosis pathway were notably downregulated compared with OSA. Conclusions: SLGP ablation suppressed AF in a chronic OSA model by sympathovagal hyperactivity inhibition. However, there were no significant changes in myocardial fibrosis.